TNF-related apoptosis-inducing ligand, interferon gamma-induced protein 10, and C-reactive protein in predicting the progression of SARS-CoV-2 infection: a prospective cohort study. (September 2022) - Tegethoff, Sina A.; Danziger, Guy; Kühn, Dennis; Kimmer, Charlotte; Adams, Thomas; Heintz, Lena; Metz, Carlos; Reifenrath, Katharina; Angresius, Rebecca; Mang, Sebastian; Rixecker, Torben; Becker, André; et al.
Highlights: Biomarkers TNF-related apoptosis-inducing ligand (TRAIL), interferon gamma-induced protein 10 (IP-10), and C-reactive protein (CRP) are correlated with COVID-19 severity TRAIL yielded lower levels and IP-10 yielded higher levels in patients with COVID-19 than in controls Obesity, CRP, and high peak IP-10 were associated with intensive care unit mortality Patients with low initial TRAIL levels more often required mechanical ventilation Including TRAIL, IP-10, and CRP in risk assessment models seems promising ABSTRACT: Background: Early prognostication of COVID-19 severity will potentially improve patient care. Biomarkers, such as TNF-related apoptosis-inducing ligand (TRAIL), interferon gamma-induced protein 10 (IP-10), and C-reactive protein (CRP), might represent possible tools for point-of-care testing and severity prediction. Methods: In this prospective cohort study, we analyzed serum levels of TRAIL, IP-10, and CRP in patients with COVID-19, compared them with control subjects, and investigated the association with disease severity. Results: A total of 899 measurements were performed in 132 patients (mean age 64 years, 40.2% females). Among patients with COVID-19, TRAIL levels were lower (49.5 vs 87 pg/ml, P  = 0.0142), whereas IP-10 and CRP showed higher levels (667.5 vs 127 pg/ml, P <0.001; 75.3 vs 1.6 mg/l, P <0.001) than healthy controls. TRAIL yielded an inverse correlation with length of hospital and intensive care unit (ICU) stay, Simplified Acute Physiology Score II, and National Early Warning Score, and IP-10 showed a positive correlation with disease severity. Multivariable regression revealed that obesity (adjusted odds ratio [aOR] 5.434, 95% confidence interval [CI] 1.005-29.38), CRP (aOR 1.014, 95% CI 1.002-1.027), and peak IP-10 (aOR 1.001, 95% CI 1.00-1.002) were independent predictors of in-ICU mortality. Conclusions: We demonstrated a correlation between COVID-19 severity and TRAIL, IP-10, and CRP. Multivariable regression showed a role for IP-10 in predicting unfavourable outcomes, such as in-ICU mortality. Trial registration: Clinicaltrials.gov, NCT04655521